A Decrease in Hemodynamic Response in the Right Postcentral Cortex Is Associated With Treatment-Resistant Auditory Verbal Hallucinations in Schizophrenia: An NIRS Study - Liang, Nana; Liu, Sha; Li, Xinrong; Wen, Dan; Li, Qiqi; Tong, Yujie; Xu, Yong (Frontiers in Neuroscience, 2022)
Background: Treatment-resistant auditory verbal hallucinations (TRAVH) might caused an increased risk of violence, suicide, and hospitalization of schizophrenia (SCZ) patients. Although neuroimaging studies have identified the neural correlates of the symptom of AVH, functional brain activity correlates particularly in patients with TRAVH remain limited. Functional near infrared spectroscopy (fNIRS) is a portable and suitable measurement, particularly in exploring brain activation during related tasks. Hence, our researchers aimed to explore the differences among the cerebral haemodynamic function in SCZ-TRAVH, schizophrenia patients without AVH (SCZ-nAVH), and healthy controls (HC), to examine neural abnormalities associated more specifically with TRAVH. Methods: A 52-channel NIRS system was used to monitor hemodynamic changes in SCZ-TRAVH patients (n=38), SCZ-nAVH patients (n=35), and HC (n=30) during a verbal fluency task (VFT). VFT performance, clinical history and symptom severity were also noted. The original fNIRS data were analysed using MATLAB to obtain the β values (the brain cortical activity response during the VFT task period); these were used to calculate Δβ (VFT β minus baseline β), which represents the degree of change in oxygenated haemoglobin caused by VFT task. Result: Our results showed that there were significant differences in Δβ values among the three groups at 26 channels (ch4, ch13-15, 18, 22, ch25-29, 32, ch35-39, ch43-51, F = 1.70 to 19.10, p < 0.043, FDR-corrected) distributed over the prefrontal-temporal cortical regions. The further pairwise comparisons showed that the Δβ values of 24 channels (ch13-15, 18, 22, 25, ch26-29, ch35-39, ch43-49, ch50-51) was significantly lower in the SCZ group (SCZ-TRAVH and/or SCZ-nAVH) than in the HC group (p < 0.026, FDR-corrected). Additionally, the abnormal activation in the ch22 of right postcentral gyrus correlated, in turn, with severity of TRAVH. Conclusion: Our findings indicate that specific regions of the prefrontal cortex may be associated with TRAVH, which may have implications for early intervention for psychosis.